2011
DOI: 10.1111/j.1529-8817.2011.00993.x
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Indicator Value of Rare Taxa Richness in Diatom-Based Stream Bioassessment1

Abstract: Despite their recognized contribution to species richness, the importance of rare taxa richness in bioassessment is unclear. This study aimed to characterize the environmental factors affecting the number of rare diatom taxa in western U.S. streams and rivers, and to evaluate whether this number can be used to differentiate streams with contrasting human disturbance. Three different categories of rare taxa were used: satellite (taxa with low occurrence and low abundance), rural (taxa with high occurrence and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Relative abundance is widely used in research on environmental assessments (Maraslioglu et al, ; Schuch et al, ; Tan et al, 2015). Gillett et al () separated all species into four groups: core species (high abundance and high occurrence) and satellite/rare species (low abundance and low occurrence), urban species (low abundance and high occurrence) and rural species (high abundance and low occurrence). Jain et al () defined species rarity from the three key properties of geographic range, habitat specificity, and local abundance, and found that the way rare species are defined changed how functional diversity is assessed.…”
Section: Discussionmentioning
confidence: 99%
“…Relative abundance is widely used in research on environmental assessments (Maraslioglu et al, ; Schuch et al, ; Tan et al, 2015). Gillett et al () separated all species into four groups: core species (high abundance and high occurrence) and satellite/rare species (low abundance and low occurrence), urban species (low abundance and high occurrence) and rural species (high abundance and low occurrence). Jain et al () defined species rarity from the three key properties of geographic range, habitat specificity, and local abundance, and found that the way rare species are defined changed how functional diversity is assessed.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases rare taxa are not recorded in the results of different publications about Turkish inland waters. However, these taxon records are important to biodiversity assessments (Gillett et al, 2011). We recommend that the species occurrences should be noted in water quality monitoring studies.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the floristic richness of diatoms in the river is a necessary, further step. These new and rare taxa significantly contribute to diatom biodiversity of the Nišava River and Serbia, though the importance of rare diatom taxa in bioassessment studies is still unclear (Potapova & Charles 2004, Gillett et al 2011. This new information increases our knowledge of the river system and the relationship between diatom species and chemical parameters, which is important for further predictions of the water quality based on the occurrence of diatoms as bioindicators, and monitoring programs.…”
Section: Distribution (Europe)mentioning
confidence: 99%